A High-Throughput Approach to Discovery: Heck-Type Reactivity with Aldehydes - Vandavasi, Jaya Kishore; Newman, Stephen G. (Synlett, 2018)
The classical Heck reaction is among the most powerful methods available for the construction of C–C bonds. Modification of this transformation to utilize diverse organohalide coupling partners has resulted in new reactions such as the silyl-Heck, aza-Heck, and boryl-Heck reactions. In contrast, modification of the olefin coupling partner is rare. For instance, use of the π-bond of an aldehyde instead of an alkene would provide ketones via a carbonyl-Heck process. This seemingly minor manipulation of the Heck reaction has proven surprisingly difficult to realize in practice. Through the use of high-throughput experimentation techniques, an efficient catalyst system for this transformation was identified, enabling the intermolecular coupling of organotriflates and aldehydes to synthesize diverse ketones.
Keywords: Heck reaction; cross-coupling; nickel; high-throughput experimentation; reaction discovery